Cost to developing countries of adapting to climate change: new methods and estimates - Margulis, S.; Narain, U.; Chinowsky, P.; Cretegny, L.; Hughes, G.; Kirshen, P.; Kuriakose, A.T.; Lange, G.M.; Nelson, Gerald C.; Neumann, J.; Nicholls, R.; Pandy, K.; et al. (World Bank, 2010)
Even with global emissions of greenhouse gases drastically reduced in the coming years, the global annual average temperature is expected to be 2°C above pre-industrial levels by 2050. A 2°C warmer world will experience more intense rainfall and more frequent and more intense droughts, floods, heat waves, and other extreme weather events. Households, communities, and planners need to put in place initiatives that “reduce the vulnerability of natural and human systems against actual and expected climate change effects” (IPCC 2007). Without such adaptation, development progress will be threatened—perhaps even reversed.